THE ROLE OF SOCIAL CLASS IN SCOTT FITZGERALD'S THE GREAT GATSBY - Mulyana Syahika, Muhammad Rizky; Trianugrah, Ferry (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2024)
The purpose of this study is the exploration and analysis of literary works that are reflective of the theory of Marxist structuralism. In The Great Gatsby, Fitz Gerald portrayed the social classes with the characteristics in the story. This research used qualitative research to collect the data. The researcher read several books and articles that described and explained the identification process with Marx's theory. As mentioned above, the object collected from The Great Gatsby by F. Scott Fitzgerald is caused by a close and interrelated relationship between Fitzgerald and his works. This research resulted and was discussed in structuration, which is focused on revealed characteristics and added comprehension theory to provide it. One of the characteristics that depicts Bourjois is Tom. It is caused by the arrogant attitude that Tom shows from the beginning of the story to the end, which is related to Fitzegerald's perspective of Borjouis. However, there is Gatsby, who comes from Proletarian and implicitly shows how Fitzegerald was before being the Bourjois. It is also explained with theories that come from his personal essay, My Personal City. The purposes of the author can be seen in the details of social phenomena that were added to his literary work, namely The Great Gatsby.